The Role of E-Customer Satisfaction as Intervening Variable in Relationship Between E-Service Quality, E-Recovery and E-Customer Loyalty of Indonesian Railroad Access Customers - Moh. Samsul Arifin; Muhammad Fikri Maulana; Amat Suroso; Suhartono; Mariam (Jurnal Sistim Informasi dan Teknologi, 2023)
In this study, the impact of eService and eRecovery Service Quality on Online Customer Satisfaction and its Implications for Online Customer Loyalty are measured. Partial Least Square (PLS) was used to evaluate information from 100 respondents who had purchased tickets using the Indonesian railway application. According to the study's findings, e-service quality, e-recovery service quality, e-service quality, e-customer satisfaction, and e-customer satisfaction all have an impact on e-customer satisfaction. These relationships also hold true for e-customer loyalty. According to the research, the developer must maintain the services offered to users through its application and switch out all slow trains with quick ones. Additionally, they should create intriguing inventions, send clients thank-you letters, ask for user reviews, and enhance their online customer service.